The Use Of E-Banking In Malaysia Among Information Technology Personnel - Puasa, Azril Sani (2002)
The problem under investigation is on the use of E-Banking in Malaysia among information technology personnel. The findings of this study will contribute to better knowledge of the factors and issues, which affect the adoption and usage of E-Banking among